PERAN ENGAGING LEADERSHIP TERHADAP KOMITMEN ORGANISASIONAL DALAM PROXIMAL WITHDRAWAL STATES - Kentami, Maria Regina Tinon Dyah; Rostiana, Rostiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Preserving competent employees is still a primary challenge for the organization today. Every company needs to make efforts to retain the employees they have. PT.X is one of the companies operating in the education sector that needs to anticipate future turnovers. This study aims to investigate the role of engaging leadership toward organizational commitment in the Proximal Withdrawal States (PWS) at PT.X. Researchers hope that by great engaging leadership, the organizational commitment will improve so that the probability of turnover will decrease. The study was administered on 295 employees at PT.X, who is a permanent employee and had worked for more than one year. This research belongs to non-experimental quantitative research. A simple regression model was conducted to process the data of this study. The results showed that engaging leadership had a significant role of 16.8% toward organizational commitment. However, based on the situation description, engaging leadership only plays a significant role in the